10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Aims To describe pregnancy outcomes in those with systemic lupus erythematosus (SLE) in Aotearoa/New Zealand. Methods We conducted a retrospective population-based cohort study using linked national datasets from 2005 to 2022. Multivariable logistic regression estimated associations between birth outcomes and timing of SLE diagnosis, end-stage kidney disease (ESKD), ethnicity, maternal age, deprivation quintile and year of parturition. Results Among 2450 females with SLE, 1532 were aged 18-45 years. There were 971 births, with a live birth rate of 96.1%. Preterm birth occurred in 19.3%, caesarean section in 36.6%, and induction in 48.1%. Births occurring after the diagnosis of SLE were associated with higher odds of preterm birth (OR 1.77, 95%CI 1.17-2.71), induction (OR 2.21, 95%CI 1.58-3.11) and ESKD (OR 23.7, 95%CI 4.05-450). Conclusions SLE is associated with increased obstetric risk in New Zealand, particularly for pregnancies after diagnosis, and among those with ESKD, with trends toward higher risk in Māori and Pacific ethnicities.